ASSESSMENT OF SERUM LEVELS AS SENSITIVE thyroid stimulating hormone EARLY DETECTION OF CANCER THYROID - Sarah Permadi, Prichilia; Saraswati, Made Ratna (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana, 2013)
Enlargement of thyroid or goiter is a general clinical problem. These cases are 5-10% may come to thyroid nodule. Thyroid cancer is thyroid gland malignancy in nodule formed. Clinically, benign thyroid nodule is difficult to thyroid nodule malignancy. The assessment of Thyroid Stimulating Hormone sensitive (TSHs) serum usually does as a screening tool to detect the enlargement and malignancy of thyroid gland which is suspected. Increases of TSH serum have a correlation with the prevalence of thyroid cancer. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: thyroid nodule, thyroid cancer, Thyroid Stimulating Hormone sensitive (TSHs)